+0  
 
0
228
1
avatar

I need help...

 

The values of a function \(f(x)\) are given in the table below.

If \(f^{-1}\) exists, then what is \(f^{-1}(f^{-1}(f^{-1}(1)))\)?

 Sep 1, 2019
 #1
avatar+111387 
+1

We actually  have the coordinates ( 1,3) (2,1) (3.5) (4,4)  (5,2)

The inverse reverses these  so we would have ( 3,1) (1,2) ( 5,3) (4,4) (2,5)

 

So  f-1(1)  =   2

 

And   f-1 ( f-1(1))  =  f-1(2) = 5

 

Finally

 

f-1 ( f-1 (f-1 (1) ))   =    f-1(5)  = 3

 

 

 

cool cool cool

 Sep 1, 2019

11 Online Users

avatar
avatar
avatar